Pengaruh Strategi Pembelajaran Dan Kemampuan Berpikir Logis Terhadap Keterampilan Menulis Argumentasi (Studi Eksperimen Pada Siswa Kelas Xi Sma Negeri 1 Lengayang) - Iskandar, Zelvi (Institut Agama Islam Negeri (iAIN) Curup, 2018)
The study is intendead to investigate the achievement of language skill of student’s who learn through cooperative learning strategy and those who learn through individual learning one. It is a qualitative research by employing experiment methode which includes two sampel of group, namely ones who follow cooperative learning strategy. Based on the findings and the investigation, it reaches the following conclusion. Firstly, teachers can choose which learning materials and strategies should be used to gain the increasment of student’s skill writing argumentation as when the level of rational thingking of student has been known. Secondly, the strategy of cooperative learning and individual learning among student’s group who have different ability in using logical thingking will result in different skill in writing argumentation. Thirdly, the improvement of argumentative writing skill can be effected by factors of learning strategy and logical thingking skill. Fourtly, the learning strategy and logical thingking skills have strong connection to the skill of writing argumentation.